Community Cultural Values and Control of Non-Communicable Disease Risk Factors: A Cross-Sectional Study - Try Ayu Patmawati; Aris Wawomeo; Irwan Budiana; Pius Kopong Tokan; Rif'atunnisa Rif'atunnisa; Aldiana Astuti; Petrus Belamirnus; Kusmiyati Kusmiyati (An Idea Nursing Journal, 2026)
Background: Lack of knowledge about diseases, suboptimal quality of services, low awareness of risk factors, and low compliance with prevention measures are problems that arise in efforts to control Non-Communicable Diseases (NCDs) in various developing countries worldwide, including Indonesia. Perceptions that are not in accordance with health science can worsen the risk factors for non-communicable diseases, which are currently a major public health problem Objective: to identify which values and cultures should be preserved, negotiated, and even changed. Methods:study is descriptive-analytical, with a cross-sectional design, to analyze community cultural values as a means of controlling non-communicable diseases. This study was conducted in Wologai village, with 79 respondents. Data were analyzed using SPSS 25 software with Spearman's Rank Correlation Coefficient . Results: Community perceptions and behaviors were significantly associated with efforts to control non-communicable disease risk factors (p-value <0.05), whereas traditional medicine, stigma and health, and community ritual and spiritual practices were not (p-value >0.05). Conclusion: Public perception and behavior contribute to NCD risk factor control but are not the primary determinants. Therefore, attention is needed to consider other factors that may also influence the success of NCD risk factor control in the community.